2013
DOI: 10.2147/ijn.s44155
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis recombinant MOMP encapsulated in PLGA nanoparticles triggers primarily T helper 1 cellular and antibody immune responses in mice: a desirable candidate nanovaccine

Abstract: Abstract:We recently demonstrated by in vitro experiments that PLGA (poly D, L-lactideco-glycolide) potentiates T helper 1 (Th1) immune responses induced by a peptide derived from the recombinant major outer membrane protein (rMOMP) of Chlamydia trachomatis, and may be a promising vaccine delivery system. Herein we evaluated the immune-potentiating potential of PLGA by encapsulating the full-length rMOMP (PLGA-rMOMP), characterizing it in vitro, and investigating its immunogenicity in vivo. Our hypothesis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…Recombinant MOMP-278 (M278) was cloned as previously reported 15 and encapsulated in PLA-PEG nanoparticles using a modified water/oil/water double emulsion evaporation technique 16,17 and then lyophilized in the presence of 5% trehalose (as a stabilizer) to obtain encapsulated-M278 (PLA-PEG-M278). Phosphate buffered saline (PBS) was similarly encapsulated in PLA-PEG to serve as a negative control (PLA-PEG-PBS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant MOMP-278 (M278) was cloned as previously reported 15 and encapsulated in PLA-PEG nanoparticles using a modified water/oil/water double emulsion evaporation technique 16,17 and then lyophilized in the presence of 5% trehalose (as a stabilizer) to obtain encapsulated-M278 (PLA-PEG-M278). Phosphate buffered saline (PBS) was similarly encapsulated in PLA-PEG to serve as a negative control (PLA-PEG-PBS).…”
Section: Methodsmentioning
confidence: 99%
“…UV-Vis was employed to ascertain M278 encapsulation within PLA-PEG as recently described 17,18 . Nanoparticles and bare M278 were each diluted in deionized water and their absorbance and spectral wavelengths were assessed using the DU 800UV/Vis spectrophotometer (Beckman Coulter, Fullerton, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan is a chitin-derived polysaccharide and has several properties that make it a useful vaccine delivery system, including its mucoadhesiveness and enhanced penetration capacity across mucosal barriers (188). Two recent studies using recombinant MOMP encapsulated in PLGA demonstrated enhanced induction of Th1 cytokines and cellular and antibody immune responses (189,190). Cambridge et al demonstrated that MOMP was expressed in the tissues and organs of mice that were intramuscularly injected with chitosan nanoparticles containing recombinant MOMP DNA (191).…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…Synthetic polymers alone do not usually possess an immunostimulatory effect, but can enhance immunization via facilitating the delivery of antigens and/or adjuvants [47]. For example, PLGA nanoparticles incorporating a recombinant major outer membrane protein of Chlamydia trachomatis ( C. trachomatis ) induced elevated numbers of CD4+ and CD8+ T cell subsets and a 64-fold higher Th1 than Th2 antibody titer [170]. Toxoid vaccines, which are based on inactivated bacterial toxins, have been widely used to promote antitoxin immunity for the prophylaxis and treatment of microbial infections.…”
Section: Antimicrobial Nanovaccinementioning
confidence: 99%